(untitled) (Annals of Medical Research, 2021)
Aim: To develop a valid measurement tool that can evaluate oral and dental health knowledge and to create a program model of oral and dental health education by using different training methods that reinforce each other.Material and Methods: The developed scale for validity and reliability study was applied to 163 kindergarten, first-grade, and second-grade students. The Scale Oral Health Knowledge for 5-8 Age Children was used in the evaluation of education. In the four-week training program, pre-test with scale, oral and dental health visual training presentations, parent education, healthy food package distribution, creative drama training, toothbrush and paste dissipation and post-test with scale were applied.Results: The scale developed consisted of 10 items and the KR-20 reliability was calculated as 0.71 and the internal consistency coefficient was calculated as 0.70. In the results of the study, there was a significant difference in favor of the last test in the experimental group (z = 4.46, p 05). Conclusion: The Scale Oral Health Knowledge for 5-8 Age Children is a valid and reliable scale. The “Multi-Component Oral Health Education Programme” is an evaluable, necessary and effective program. In order to provide a permanent oral hygiene education, it is important to use training program preparation by a multidisciplinary team different training methods and materials that reinforce each other over a long period of time and to evaluate the adequacy of education.